A solar photovoltaic mesh belt and preparation method thereof
By pretreating and titanium plating on the steel wire, combining microwave equipment and ultrasonic impact technology, a solar photovoltaic mesh belt with excellent wear resistance, corrosion resistance and oxidation resistance is prepared, which solves the aging and corrosion of mesh belt in harsh environments. Problem, extending service life.
Patent Information
- Application Number
- CN202410276923.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-03-12
AI Technical Summary
Solar photovoltaic grids are prone to aging and corrosion problems under harsh environments and climatic conditions, shortening their service life.
By pretreating the steel wire, spraying titanium powder and plating the surface, combining microwave equipment and ultrasonic impact technology, a solar photovoltaic mesh belt with excellent wear resistance, corrosion resistance and oxidation resistance is prepared.
It significantly improves the wear resistance, corrosion resistance and oxidation resistance of solar photovoltaic mesh belts, extends the service life, and is suitable for a wide range of market applications.
Smart Images

Figure CN118360602B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material processing and production, in particular to a solar photovoltaic mesh belt and a preparation method thereof. Background Art
[0002] Solar photovoltaic mesh belt, also known as solar silicon wafer sintering mesh belt, is used for conveying solar silicon wafer sintering process. Solar photovoltaic mesh belt is an important part of green energy production and a key force to achieve sustainable development.
[0003] The service life of solar photovoltaic mesh belts is related to factors such as the use environment and climatic conditions. In harsh environmental and climatic conditions, such as high humidity, salt spray, ultraviolet rays, etc., photovoltaic mesh belts are prone to aging, corrosion and other problems, thus shortening their service life. Therefore, how to effectively improve the quality of solar photovoltaic mesh belts has become an important issue that needs to be urgently solved in the material processing industry.
[0004] Therefore, the present invention provides a solar photovoltaic mesh belt and a preparation method thereof, which are used to solve the above-mentioned related technical problems. Summary of the invention
[0005] The purpose of the present invention is to provide a solar photovoltaic mesh belt and a preparation method thereof. The solar photovoltaic mesh belt prepared by the present invention not only has excellent wear resistance, but also has excellent corrosion resistance; and is also antioxidant.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a solar photovoltaic mesh belt, comprising the following steps:
[0008] S1. Taking steel wires for making solar photovoltaic mesh belts and pre-treating the steel wires;
[0009] S2, spraying titanium powder liquid evenly on the surface of the pretreated steel wire, then drying, and repeating the spraying 3 to 4 times to obtain a titanium-coated steel wire;
[0010] S3, placing the obtained titanium-coated steel wire in a microwave device for surface titanium plating to obtain a titanium-coated steel wire;
[0011] S4. After polishing the titanium-plated steel wire, weave it into a solar photovoltaic mesh belt.
[0012] The present invention is further configured as follows: in the step S1, the material of the steel wire is any one of SUS314 and SUS316L.
[0013] The present invention is further configured as follows: in step S1, the process of pre-treating the taken steel wire is as follows:
[0014] Place the steel wire in an appropriate amount of degreasing agent, shake the steel wire continuously, and treat it at 40-50℃ for 20-30 minutes;
[0015] Remove the steel wire, rinse it 2 to 3 times with distilled water, and then let it dry naturally.
[0016] The present invention is further configured as follows: the degreasing agent is made of the following raw materials in parts by weight: 10 to 20 parts of a surfactant, 8 to 12 parts of trisodium methylglycine diacetate, 10 to 20 parts of sodium carbonate, 10 to 20 parts of conical stainless steel particles and 25 to 35 parts of deionized water;
[0017] The preparation process of the degreasing agent is as follows:
[0018] Accurately weigh surfactant, trisodium methylglycine diacetate, sodium carbonate, conical stainless steel particles and deionized water and set aside;
[0019] The surfactant, trisodium methylglycine diacetate, sodium carbonate, conical stainless steel particles and deionized water are placed in a stirring device and fully mixed for 10 to 15 minutes at 320 to 450 r / min to obtain a degreasing agent.
[0020] The present invention is further configured as follows: the surfactant is selected from any one of the non-ionic surfactant APG0810 and the non-ionic surfactant JFC-2G.
[0021] The present invention is further configured as follows: the particle size of the conical stainless steel particles is 20 to 30 um.
[0022] The present invention is further configured as follows: in step S2, the titanium powder liquid is prepared by mixing and dissolving titanium hydride and anhydrous ethanol at a solid-liquid ratio of 0.06 to 0.1 g / mL.
[0023] The present invention is further configured as follows: in step S3, the process of titanium plating the surface is as follows:
[0024] The microwave equipment was evacuated to 3.5-5.5 Pa and argon gas was introduced;
[0025] The titanium-coated steel wire is heated to 700-840°C by microwave, and kept at this temperature for 40-50 minutes, and then cooled to room temperature;
[0026] The titanium-coated steel wire is subjected to ultrasonic impact. After the ultrasonic impact is completed, the temperature is continuously raised to 700-840° C. by microwave, and the temperature is kept for 120-130 minutes. Finally, the titanium-coated steel wire is cooled to room temperature to obtain the titanium-coated steel wire.
[0027] The present invention is further configured as follows: the ultrasonic impact frequency of the ultrasonic impact is 1000-2000 times / s, the impact end moving speed is 1-5 mm / s, and the impact energy is 0.01-0.05 J.
[0028] The second aspect of the present invention: also provides a solar photovoltaic mesh belt prepared by the above method.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The preparation method of the solar photovoltaic mesh belt provided by the present invention comprises the following steps: pre-treating the steel wire, uniformly spraying titanium powder liquid on the surface of the pre-treated steel wire to obtain titanium-coated steel wire, and then placing the obtained titanium-coated steel wire in a microwave device for surface titanium plating to obtain titanium-coated steel wire, and finally polishing the titanium-coated steel wire and weaving it into a solar photovoltaic mesh belt; the solar photovoltaic mesh belt prepared by the present invention has not only excellent wear resistance, but also excellent corrosion resistance; and is also resistant to oxidation. The solar photovoltaic mesh belt produced by the present invention has a broader market prospect and is more suitable for promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 It is a statistical diagram of the average wear amount of the present invention;
[0033] Figure 2 It is a statistical diagram of the moderate salt spray test of the present invention;
[0034] Figure 3 It is a statistical diagram of the oxidation weight gain of the present invention. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] This embodiment provides a method for preparing a solar photovoltaic mesh belt, comprising the following steps:
[0038] S1. Take steel wires for weaving solar photovoltaic mesh belts and pre-treat the steel wires.
[0039] Among them, the material of the steel wire is SUS314.
[0040] In addition, the process of pre-treating the obtained steel wire is as follows:
[0041] Place the steel wire in an appropriate amount of degreasing agent, shake the steel wire continuously, and treat it at 40℃ for 20 minutes;
[0042] Remove the steel wire, rinse it twice with distilled water, and then let it dry naturally.
[0043] Further, the degreasing agent is made of the following raw materials in parts by weight: 10 parts of a surfactant, 8 parts of trisodium methylglycine diacetate, 10 parts of sodium carbonate, 10 parts of conical stainless steel particles and 25 parts of deionized water;
[0044] The preparation process of degreasing agent is as follows:
[0045] Accurately weigh surfactant, trisodium methylglycine diacetate, sodium carbonate, conical stainless steel particles and deionized water and set aside;
[0046] A surfactant, trisodium methylglycine diacetate, sodium carbonate, conical stainless steel particles and deionized water were placed in a stirring device and fully mixed at 320 r / min for 10 minutes to obtain a degreasing agent.
[0047] Furthermore, the surfactant is non-ionic surfactant APG0810.
[0048] The particle size of the conical stainless steel particles is 20um.
[0049] S2. Evenly spray titanium powder liquid on the surface of the pretreated steel wire, then dry it, and repeat the spraying 3 times to obtain a titanium-coated steel wire.
[0050] The titanium powder liquid is prepared by mixing and dissolving titanium hydride and anhydrous ethanol at a solid-liquid ratio of 0.06 g / mL.
[0051] S3, placing the obtained titanium-coated steel wire in a microwave device for surface titanium plating to obtain a titanium-coated steel wire.
[0052] Among them, the process of surface titanium plating is as follows:
[0053] The microwave equipment was evacuated to 3.5 Pa and argon gas was introduced;
[0054] The titanium-coated steel wire was heated to 700°C by microwave, kept at this temperature for 40 min, and then cooled to room temperature;
[0055] The titanium-coated steel wire was subjected to ultrasonic impact. After the ultrasonic impact was completed, the temperature was continued to be raised to 700° C. by microwave, and the temperature was kept for 120 minutes. Finally, the titanium-coated steel wire was cooled to room temperature to obtain the titanium-coated steel wire.
[0056] In addition, the ultrasonic impact frequency of the ultrasonic impact is 1000 times / s, the impact end moving speed is 1 mm / s, and the impact energy is 0.01J.
[0057] S4. After polishing the titanium-plated steel wire, weave it into a solar photovoltaic mesh belt.
[0058] Embodiment 2:
[0059] This embodiment provides a method for preparing a solar photovoltaic mesh belt, comprising the following steps:
[0060] S1. Take steel wires for weaving solar photovoltaic mesh belts and pre-treat the steel wires.
[0061] Among them, the material of the steel wire is SUS314.
[0062] In addition, the process of pre-treating the obtained steel wire is as follows:
[0063] Place the steel wire in an appropriate amount of degreasing agent, shake the steel wire continuously, and treat it at 45℃ for 25 minutes;
[0064] The steel wire was removed and rinsed with distilled water for 3 times and then allowed to dry naturally.
[0065] Further, the degreasing agent is made of the following raw materials in parts by weight: 15 parts of a surfactant, 10 parts of trisodium methylglycine diacetate, 15 parts of sodium carbonate, 15 parts of conical stainless steel particles and 30 parts of deionized water;
[0066] The preparation process of degreasing agent is as follows:
[0067] Accurately weigh surfactant, trisodium methylglycine diacetate, sodium carbonate, conical stainless steel particles and deionized water and set aside;
[0068] A surfactant, trisodium methylglycine diacetate, sodium carbonate, conical stainless steel particles and deionized water were placed in a stirring device and fully mixed at 370 r / min for 12 minutes to obtain a degreasing agent.
[0069] Furthermore, the surfactant is selected from nonionic surfactant JFC-2G.
[0070] The particle size of the conical stainless steel particles is 25um.
[0071] S2. Evenly spray the titanium powder liquid on the surface of the pretreated steel wire, then dry it, and repeat the spraying 4 times to obtain a titanium-coated steel wire.
[0072] The titanium powder liquid is prepared by mixing and dissolving titanium hydride and anhydrous ethanol at a solid-liquid ratio of 0.08 g / mL.
[0073] S3, placing the obtained titanium-coated steel wire in a microwave device for surface titanium plating to obtain a titanium-coated steel wire.
[0074] Among them, the process of surface titanium plating is as follows:
[0075] The microwave equipment was evacuated to 4.5 Pa and argon gas was introduced;
[0076] The titanium-coated steel wire was heated to 760°C by microwave, kept at this temperature for 45 min, and then cooled to room temperature;
[0077] The titanium-coated steel wire is subjected to ultrasonic impact. After the ultrasonic impact is completed, the temperature is continued to be raised to 760° C. by microwave, and the temperature is kept for 120 to 130 minutes. Finally, the titanium-coated steel wire is cooled to room temperature to obtain the titanium-coated steel wire.
[0078] In addition, the ultrasonic impact frequency of the ultrasonic impact is 1500 times / s, the impact end moving speed is 2mm / s, and the impact energy is 0.02J.
[0079] S4. After polishing the titanium-plated steel wire, weave it into a solar photovoltaic mesh belt.
[0080] Embodiment 3:
[0081] This embodiment provides a method for preparing a solar photovoltaic mesh belt, comprising the following steps:
[0082] S1. Take steel wires for weaving solar photovoltaic mesh belts and pre-treat the steel wires.
[0083] Among them, the material of the steel wire is SUS314.
[0084] In addition, the process of pre-treating the obtained steel wire is as follows:
[0085] Place the steel wire in an appropriate amount of degreasing agent, shake the steel wire continuously, and treat it at 50℃ for 30 minutes;
[0086] The steel wire was removed and rinsed with distilled water for 3 times and then allowed to dry naturally.
[0087] Further, the degreasing agent is made of the following raw materials in parts by weight: 20 parts of surfactant, 12 parts of methylglycine diacetate trisodium salt, 20 parts of sodium carbonate, 20 parts of conical stainless steel particles and 35 parts of deionized water;
[0088] The preparation process of degreasing agent is as follows:
[0089] Accurately weigh surfactant, trisodium methylglycine diacetate, sodium carbonate, conical stainless steel particles and deionized water and set aside;
[0090] A surfactant, trisodium methylglycine diacetate, sodium carbonate, conical stainless steel particles and deionized water were placed in a stirring device and fully mixed at 450 r / min for 15 minutes to obtain a degreasing agent.
[0091] Furthermore, the surfactant is non-ionic surfactant APG0810.
[0092] The particle size of the conical stainless steel particles is 30um.
[0093] S2. Evenly spray the titanium powder liquid on the surface of the pretreated steel wire, then dry it, and repeat the spraying 4 times to obtain a titanium-coated steel wire.
[0094] The titanium powder liquid is prepared by mixing and dissolving titanium hydride and anhydrous ethanol at a solid-liquid ratio of 0.1 g / mL.
[0095] S3, placing the obtained titanium-coated steel wire in a microwave device for surface titanium plating to obtain a titanium-coated steel wire.
[0096] Among them, the process of surface titanium plating is as follows:
[0097] The microwave equipment was evacuated to 5.5 Pa and argon gas was introduced;
[0098] The titanium-coated steel wire was heated to 840°C by microwave, kept at this temperature for 50 min, and then cooled to room temperature;
[0099] The titanium-coated steel wire was subjected to ultrasonic impact. After the ultrasonic impact was completed, the temperature was continued to be raised to 840° C. by microwave, and the temperature was kept for 130 minutes. Finally, the titanium-coated steel wire was cooled to room temperature to obtain the titanium-coated steel wire.
[0100] In addition, the ultrasonic impact frequency of the ultrasonic impact is 2000 times / s, the impact end moving speed is 5 mm / s, and the impact energy is 0.05J.
[0101] S4. After polishing the titanium-plated steel wire, weave it into a solar photovoltaic mesh belt.
[0102] Comparative Example 1: The solar photovoltaic mesh belt and the preparation method thereof provided in this embodiment are substantially the same as those in Example 1, with the main difference being that the degreasing agent in this embodiment is replaced by a 2% sodium hydroxide solution.
[0103] Comparative Example 2: The solar photovoltaic mesh belt and its preparation method provided in this embodiment are substantially the same as those in Example 1, with the main difference being that microwave treatment is not performed in this embodiment, that is, ultrasonic impact is directly used.
[0104] Comparative Example 3: The solar photovoltaic mesh belt and the preparation method thereof provided in this embodiment are substantially the same as those in Example 1, with the main difference being that ultrasonic impact is not performed in this embodiment, that is, microwave treatment is directly and continuously performed.
[0105] Effect test
[0106] The solar photovoltaic mesh belts prepared by the methods of Examples 1 to 3 of the present invention are respectively recorded as Experimental Examples 1 to 3; the solar photovoltaic mesh belts prepared by the methods of Comparative Examples 1 to 3 are recorded as Comparative Examples 1 to 3; and the performance of each group of solar photovoltaic mesh belt samples is then tested.
[0107] Test 1. Wear test and result analysis:
[0108] The average wear amount of 2 mm thick titanium-plated steel wire in each group of solar photovoltaic mesh belt samples was measured using a conventional friction and wear test method in an air environment at room temperature, and the relevant data are recorded in Table 1.
[0109] Table 1: Test data record table
[0110] Group <![CDATA[Average wear amount (mm 3 )]]> Example 1 Group 0.18 Example 2 Group 0.18 Example 3 Group 0.17 Comparison group 1 0.24 Comparison of 2 groups 0.28 Comparison of 3 groups 0.26
[0111] From Table 1 and Figure 1 It can be seen that compared with the control group, the methods of Examples 1 to 3 can significantly reduce the average wear amount; at the same time, the difference between the example groups is not obvious. The above results show that the methods of Examples 1 to 3 have a significant effect on improving the wear resistance of solar photovoltaic mesh belts.
[0112] In order to verify the effect of this method, experiments of Comparative Examples 1 to 3 were set up.
[0113] The main difference between the methods of comparative example 1 and example 1 is that the degreasing agent is replaced by 2% sodium hydroxide solution. Compared with the group of example 1, it is found that the average wear amount of the comparative example 1 group increases by 0.06 mm. 3 The results show that the degreasing agent plays a role in improving the wear resistance of solar photovoltaic mesh belts.
[0114] The main difference between the method of comparative example 2 and example 1 is that microwave treatment is not performed, that is, ultrasonic impact is directly used. Compared with the group of example 1, it is found that the average wear amount of the comparative example 2 group increases by 0.1 mm 3 The results show that microwave treatment plays an important role in improving the wear resistance of solar photovoltaic mesh belts.
[0115] The main difference between the method of comparative example 3 and example 1 is that the ultrasonic impact is not performed, that is, the microwave treatment is directly and continuously performed. Compared with the group of example 1, it is found that the average wear amount of the comparative example 3 group increases by 0.08mm 3The results show that ultrasonic impact plays a certain role in improving the wear resistance of solar photovoltaic mesh belts.
[0116] Test 2: Corrosion resistance test and result analysis:
[0117] The neutral salt spray limit test (CASS) was carried out according to the testing standard of GB / T10125-2012. The test results were evaluated according to GB / T6461-2002 "Rating of samples and test pieces of metal and other inorganic coatings on metal substrates after corrosion tests" until the surface reached level 9. The relevant data are recorded in Table 2.
[0118] Table 2: Test data record table
[0119] Group Moderate salt spray (h) Example 1 Group 250 Example 2 Group 245 Example 3 Group 247 Comparison group 1 150 Comparison of 2 groups 50 Comparison of 3 groups 60
[0120] From Table 2 and Figure 2 It can be seen that compared with the control group, the methods of Examples 1 to 3 can significantly improve the corrosion resistance; at the same time, the difference between the example groups is not obvious. The above results show that the methods of Examples 1 to 3 have a significant effect on improving the corrosion resistance of solar photovoltaic mesh belts.
[0121] In order to verify the effect of this method, experiments of Comparative Examples 1 to 3 were set up.
[0122] The main difference between the methods of comparative example 1 and example 1 is that the degreasing agent is replaced by 2% sodium hydroxide solution. Compared with the group of example 1, it is found that the moderate salt spray time of the comparative example 1 group is reduced by 100h. This result shows that the degreasing agent has an effect on improving the corrosion resistance of the solar photovoltaic mesh belt.
[0123] The main difference between the method of comparative example 2 and example 1 is that microwave treatment is not performed, that is, ultrasonic impact is directly used. Compared with the group of example 1, it is found that the moderate salt spray time of comparative example 2 group is reduced by 200h. This result shows that microwave treatment plays an important role in improving the corrosion resistance of solar photovoltaic mesh belts.
[0124] The main difference between the method of comparative example 3 and example 1 is that ultrasonic impact is not performed, that is, microwave treatment is directly and continuously performed. Compared with the group of example 1, it is found that the moderate salt spray time of the comparative example 3 group is reduced by 190h. This result shows that ultrasonic impact plays a certain role in improving the corrosion resistance of solar photovoltaic mesh belts.
[0125] Test 3, Antioxidant performance test and result analysis:
[0126] After constant temperature oxidation in air at 1000℃ for 100h, calculate the oxidation weight gain per unit area and record the relevant data in Table 3.
[0127] Table 3: Test data record table
[0128] Group <![CDATA[Oxidation weight gain (mg / cm 2 )]]> Example 1 Group 1.1 Example 2 Group 1.2 Example 3 Group 1.1 Comparison group 1 1.5 Comparison of 2 groups 2.0 Comparison of 3 groups 1.8
[0129] From Table 3 and Figure 3 It can be seen that compared with the control group, the methods of Examples 1 to 3 can significantly improve the antioxidant performance; at the same time, the difference between the example groups is not obvious. The above results show that the methods of Examples 1 to 3 have a significant effect on improving the antioxidant performance of solar photovoltaic mesh belts.
[0130] In order to verify the effect of this method, experiments of Comparative Examples 1 to 3 were set up.
[0131] The main difference between the methods of Comparative Example 1 and Example 1 is that the degreasing agent is replaced by 2% sodium hydroxide solution. Compared with Example 1, the oxidation weight gain of Comparative Example 1 increased by 0.4 mg / cm 2 The results show that the degreasing agent plays a role in improving the antioxidant properties of solar photovoltaic mesh belts.
[0132] The main difference between the method of comparative example 2 and example 1 is that microwave treatment is not performed, that is, ultrasonic impact is directly used. Compared with the group of example 1, it is found that the oxidation weight gain of the comparative example 2 group increases by 0.9 mg / cm 2 The results show that microwave treatment plays an important role in improving the antioxidant properties of solar photovoltaic mesh belts.
[0133] The main difference between the method of comparative example 3 and example 1 is that the method does not perform ultrasonic impact, that is, the microwave treatment is directly performed continuously. Compared with the group of example 1, it is found that the oxidation weight gain of the comparative example 3 group increases by 0.7 mg / cm 2 The results show that ultrasonic impact plays a certain role in improving the antioxidant properties of solar photovoltaic mesh belts.
[0134] From the above, it can be seen that the solar photovoltaic mesh belt prepared by the present invention not only has excellent wear resistance, but also has excellent corrosion resistance and is also resistant to oxidation. This shows that the solar photovoltaic mesh belt produced by the present invention has a broader market prospect and is more suitable for promotion.
[0135] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0136] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a solar photovoltaic mesh belt, characterized in that: The following steps are involved: S1. Taking steel wires for making solar photovoltaic mesh belts and pre-treating the steel wires; The process of pre-treating the steel wire is as follows: Place the steel wire in an appropriate amount of degreasing agent, shake the steel wire continuously, and treat it at 40-50℃ for 20-30 minutes; Take out the steel wire, rinse it with distilled water 2-3 times, and then let it dry naturally; The degreasing agent is made of the following raw materials in parts by weight: 10 to 20 parts of a surfactant, 8 to 12 parts of trisodium methylglycine diacetate, 10 to 20 parts of sodium carbonate, 10 to 20 parts of conical stainless steel particles and 25 to 35 parts of deionized water; The preparation process of the degreasing agent is as follows: Accurately weigh surfactant, trisodium methylglycine diacetate, sodium carbonate, conical stainless steel particles and deionized water and set aside; The surfactant, trisodium salt of methylglycine diacetate, sodium carbonate, conical stainless steel particles and deionized water are placed in a stirring device, and fully mixed for 10 to 15 minutes at 320 to 450 r / min to obtain a degreasing agent; S2, spraying titanium powder liquid evenly on the surface of the pretreated steel wire, then drying, and repeating the spraying 3 to 4 times to obtain a titanium-coated steel wire; The titanium powder liquid is prepared by mixing and dissolving titanium hydride and anhydrous ethanol at a solid-liquid ratio of 0.06 to 0.1 g / mL; S3, placing the obtained titanium-coated steel wire in a microwave device for surface titanium plating to obtain a titanium-coated steel wire; The process of titanium plating on the surface is as follows: The microwave equipment was evacuated to 3.5-5.5 Pa and argon gas was introduced; The titanium-coated steel wire is heated to 700-840°C by microwave, and kept at this temperature for 40-50 minutes, and then cooled to room temperature; The titanium-coated steel wire is subjected to ultrasonic impact, and after the ultrasonic impact is completed, the temperature is continuously raised to 700-840° C. by microwave, and the temperature is kept for 120-130 minutes, and finally cooled to room temperature to obtain the titanium-coated steel wire; The ultrasonic impact frequency of the ultrasonic impact is 1000-2000 times / s, the impact end moving speed is 1-5 mm / s, and the impact energy is 0.01-0.05 J; S4. After polishing the titanium-plated steel wire, it can be woven into a solar photovoltaic mesh belt.
2. A method for preparing a solar photovoltaic mesh belt according to claim 1, characterized in that: In the step S1, the material of the steel wire is any one of SUS314 and SUS316L.
3. A method for preparing a solar photovoltaic mesh belt according to claim 1, characterized in that: The surfactant is selected from any one of the nonionic surfactant APG0810 and the nonionic surfactant JFC-2G.
4. A method for preparing a solar photovoltaic mesh belt according to claim 1, characterized in that: The particle size of the conical stainless steel particles is 20-30 um.
5. A solar photovoltaic mesh belt prepared by the method for preparing a solar photovoltaic mesh belt as claimed in any one of claims 1 to 4.
Citation Information
Patent Citations
Ultrasonic vibration activation assisted microwave sintering furnace
CN104729294A
Detergent for metal surface and method for deterging metal surface by using the same
JP2004175871A
Composition for coating
KR1020180020456A